Effect of high-pressure sintering on snow density evolution: experiments and results. Issue 272 (6th December 2022) - Hong, Jialin; Talalay, Pavel; Man, Teng; Li, Yazhou; Fan, Xiaopeng; Li, Chuanjin; Zhang, Nan
Abstract: Very few studies have emphasized the effects of high-pressure sintering on snow density evolution, even though snow as a type of engineering material is widely used in construction engineering in cold regions for snow pavement, snow runway and polar infrastructure. This study presents new experimental results of snow densification under high pressures of up to 100 MPa for a temperature range from −3.5 to −17.3°C and uniaxial compression at the temperature of −10°C and constant strain rates from 5 × 10 −4 to 10 −1 s −1 . Results reveal that density evolution of snow to ice under high-pressure sintering can be achieved in a wide temperature range within a duration as short as 5 min. The compressive strength of snow-sintered ice was ~1.2–2.2 times as large as that of water-frozen ice reported by previous work. The orthogonal experiment showed that pressure is a more significant factor affecting the final density in comparison with sintering temperature and time. The increased rates of ice fabrication, low limitations on temperature and reliable sintered snow strength indicate that snow-ice engineering, such as airport construction in Greenland and Antarctica, can be improved by high-pressure sintering of snow to overcome the harsh environment.